The Effect Of Discovery Models With Blended Learning Strategies Assisted By Crossword Puzzle Media On Understanding Physics Concepts - Ois Bokingo; Supartin Supartin; Abdul Haris Odja (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to see the effect of the application of discovery learning models with blended learning strategies assisted by Crossword Puzzle media on the ability to understand students' physics concepts by choosing. This study used a pre-experimental method with a one-shot case study design consisting of 1 experimental class as a sample class which was carried out at SMP Negeri 1 Botupingge. The data obtained were in the form of understanding students' physics concepts on the material of vibration, waves, and sound which were netted using a multiple-choice test sheet as many as 20 items. The overall research results show that the application of discovery learning models with blended learning strategies assisted by Crossword Puzzle media has a significant effect on students' ability to understand physics concepts which is shown by proving the hypothesis test that the value of t table> t count which states that the lowest student learning outcomes are 75, where from the total sample of 69 respondents, 82.61% or 57 respondents scored above 75.